2010
DOI: 10.1093/ageing/afp221
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality in men compared with women following a hip fracture. National analysis of comedications, comorbidity and survival

Abstract: excess mortality among male patients cannot be explained by controlling for known comorbidity and medications. Besides gender, we found higher age and multimorbidity to be related to an increased risk of dying within the first year after fracture; acute complications might be one of the explanations. This study emphasises the need for particular rigorous postoperative diagnostic evaluation and treatment of comorbid conditions in the male hip fracture patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
261
6
15

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 453 publications
(324 citation statements)
references
References 26 publications
42
261
6
15
Order By: Relevance
“…Therefore, the study findings gave a review without taking special clinical situations into consideration. In general, intertrochanteric fracture treatment includes patients with advanced age, and other factors such as social dependence, cachexia, anemia, cognitive dysfunction, and additional comorbidities lead to a high mortality rate [7,19,29,32,42]. Despite the potential for bias, our data suggest the AO/ OTA classification is widely used in Germany (65%-88% of hospitals) and other instability criteria (lateral wall breach, detached greater trochanter, comminution of the posteromedial cortex) played a secondary role.…”
Section: Resultsmentioning
confidence: 76%
“…Therefore, the study findings gave a review without taking special clinical situations into consideration. In general, intertrochanteric fracture treatment includes patients with advanced age, and other factors such as social dependence, cachexia, anemia, cognitive dysfunction, and additional comorbidities lead to a high mortality rate [7,19,29,32,42]. Despite the potential for bias, our data suggest the AO/ OTA classification is widely used in Germany (65%-88% of hospitals) and other instability criteria (lateral wall breach, detached greater trochanter, comminution of the posteromedial cortex) played a secondary role.…”
Section: Resultsmentioning
confidence: 76%
“…The larger-sized implants provide greater biomechanical stability than smaller-diameter implants [42], which aids in fracture healing. Despite these advantages in implant selection and screw fixation being more common in men, data from hip fracture studies suggest men continue to experience worse overall morbidity and mortality than women [28].…”
Section: Fracture Healingmentioning
confidence: 99%
“…For instance, an association has been found between males and an increase in postoperative mortality in pulmonary resection and hip replacement. [6][7][8] Males have also been associated with other adverse outcomes following noncardiovascular surgery, such as increased intensive care unit (ICU) admissions and rates of sepsis. 9 In a study of surgical ICU patients, males were shown to have a poorer prognosis compared with females.…”
Section: Résumémentioning
confidence: 99%